Papillary thyroid carcinoma with nodular fasciitis-like stroma: A rare variant with distinctive morphology - Kavita Mardi (Wolters Kluwer Medknow Publications, 2017)
Papillary thyroid carcinoma (PTC) is a common malignancy with multiple variants, some of which are rarely encountered in routine surgical pathology practice. PTC with exuberant nodular fasciitis-like stroma or PTC with fibromatosis-like stroma is one such variant. This tumor is characterized by an abundant stromal component with an intervening epithelial component with the typical morphologic features of PTC. We describe gross and histopathological features of this rare variant of papillary carcinoma in a 38-year-old female and review the literature. We also discuss the importance of a thorough search for epithelial components within any fibroproliferative lesion of the thyroid and address the diagnostic difficulties created by the tumor's extensive stromal component. Given the rarity of this condition, the experience gained from the present case is a useful addition to the current knowledge on disease prognostication and management.